2011
DOI: 10.4081/reumatismo.2005.154
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in rheumatoid arthritis: analysis of hospital discharge records

Abstract: Objective: Arthritis is often associated with comorbidities. For many of them, such as hypertension, cardiovascular disease, chronic pulmonary disease, and upper gastrointestinal disease, arthritis and its treatment may also represent a risk factor. This study is concerned with an evaluation of the frequency of comorbidities in a cohort of patients with rheumatoid arthritis (RA). Methods: The discharge diagnoses of patients with RA during the period 1 January 1997 to 31 December 2000 were retrieved from the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Comorbidity is the norm rather than the exception in RA ( 8 ). Nearly, a third of patients have at least on comorbidity at the onset of RA with eventual involvement of nearly 80% patients during follow-up ( 4 , 9 ). A patient with established RA has on average two comorbidities ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comorbidity is the norm rather than the exception in RA ( 8 ). Nearly, a third of patients have at least on comorbidity at the onset of RA with eventual involvement of nearly 80% patients during follow-up ( 4 , 9 ). A patient with established RA has on average two comorbidities ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of comorbid conditions with RA vary across different countries from 3% to 60% (2, 3). However, certain studies have reported a high prevalence (up to 80%) of one or more comorbid conditions (4). Effective management of RA has improved the survival rate, but the presence of associated comorbidity has a negative impact on the outcome (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In addition, a higher updated CCI was found to be associated with an elevated risk of mortality after ICU admission using the multivariate Cox proportional hazards model. Given that nearly 80% of patients with RA suffer from comorbidities [52,53], a higher updated CCI, which was developed for the prediction of hospital mortality [19,20], might be a helpful predictor of poor prognosis in patients with RA after ICU admission. In the current study, the majority of RA patients were treated with mechanical ventilation and vasopressor therapy after ICU admission.…”
Section: Discussionmentioning
confidence: 99%